'Nie sommer nie': Sociohistorical and formal comparative considerations in the rise and maintenance of the modern Afrikaans negation system - Biberauer, Theresa (Stellenbosch Papers in Linguistics Plus, 2016)
This article has three major objectives. Firstly, it aims to describe and account for the peculiarity of the modern Afrikaans negative concord marker nie2 in the familiar Western European context. I appeal to Roberge’s (2000) diachronic proposals as the initial starting point for this oddness, showing how nie2’s putative origins as a discourse-oriented particle are synchronically reflected in the modern language, producing, among other things, what appears to be inertness in the context of Jespersen’s Cycle. This inertness leads to the interface-driven hypothesis that systems in which a structurally very high element becomes grammaticalised as a sentential Negative Concord element will not progress to the next stage of Jespersen’s Cycle, i.e. a structurally very high Negative Concord element will never take over as the “real” negation element. The article’s second objective is to demonstrate, on the basis of data from Brazilian Portuguese, Santomé, and a subset of Bantu languages, that the predictions of this hypothesis appear to be correct. At the same time, I show how crucial it is to distinguish the cyclic negation-reinforcing developments associated with Jespersen’s Cycle from non-cyclic reinforcement developments; as they may draw on the same lexical resources, this can be a challenging task, particularly where less well-studied languages are the object of investigation. The final part of the article broadens the focus, considering Afrikaans’s overall negation profile in the context of negation typology and learnability. The conclusion drawn here is that this system, which owes some of its properties to prescriptive stipulations, is a highly unusual and possibly not even naturally acquirable one.